Response of Retinal Pigment Epithelium (RPE)‐Choroid Explants to Thermal Stimulation Therapy of the RPE (TSR). Issue 3 (21st June 2020) - Richert, Elisabeth; Papenkort, Julia; Klettner, Alexa; Tode, Jan; Koinzer, Stefan; Brinkmann, Ralf; Fink, Christine; Roeder, Thomas; Lucius, Ralph; Roider, Johann
Abstract : Background and Objectives: The thermal stimulation therapy of the retinal pigment epithelium (TSR) is a sublethal laser technique for thermal stimulation of the retinal pigment epithelium (RPE)‐Bruch's membrane (BrM)‐complex. The aim of this study was to investigate the influence of TSR on the release of age‐related macular degeneration (AMD)‐relevant cell mediators. Study Design/Materials and Methods: Porcine RPE‐BrM‐choroid explants were irradiated with a 532 nm continuous wave laser using different spot sizes (100–300 µm, duration 100 milliseconds, 15–100 mW). Cell death was investigated by calcein staining. Explants were treated with grids of sublethal spots and cultivated in modified Ussing chambers. The effect on matrix metalloproteinase‐2 (MMP‐2) and ‐9 was investigated by zymography and quantitative reverse transcription polymerase chain reaction. Secretion of vascular endothelial growth factor (VEGF), pigment epithelium derived factor (PEDF), and transforming growth factor‐β (TGF‐β) was analyzed by enzyme‐linked immunosorbent assay and expression of HSP70 was examined by western blot. Integrity of the RPE/BrM‐complex was analyzed by scanning electron microscopy. Results: Laser powers of 15 mW (100 µm) and 45 mW (300 µm) did not induce RPE cell death. The integrity of the RPE/BrM‐complex was not impaired after TSR. After TSR with 300 µm spot size, we observed a significant increase of active MMP‐2 in the basal compartments. The content of PEDF significantly increased in treated explants in both compartments with 100 and 300 µm spot sizes. VEGF and TGF‐β secretion was not triggered by TSR. Conclusions: TSR represents a possible RPE stimulating treatment for dry AMD. TSR increases the basal release of active MMP‐2, which might reverse age‐related thickening of BrM. VEGF secretion was not triggered by TSR while anti‐angiogenic PEDF was increased, indicating an induction of an anti‐angiogenic and neuroprotective environment. Lasers Surg. Med. © 2020 Wiley Periodicals LLC